Treatment of Antimony-Rich Waste Streams - Avdić, Nurudin; Müller-Czygan, Günter (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2013)
The use of antimony in various chemical industries represents a potential source of environmental pollution, that occurs by discharg of untreated wastewater generated in the watercourses. Another sources of this pollutants can be individual sources from improper recycling of products containing antimony as, for example, of old batteries containing antimony in the bars and in the electrolyte. Here, it is suggested to extract antimony from waste water, with the possibility of application to different flows and concentrations of metals.